2015
DOI: 10.1016/j.socscimed.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Are bad health and pain making us grumpy? An empirical evaluation of reporting heterogeneity in rating health system responsiveness

Abstract: This paper considers the influence of patients' characteristics on their evaluation of a health system's responsiveness, that is, a system's ability to respond to the legitimate expectations of potential users regarding non-health enhancing aspects of care (Valentine et al. 2003a). Since responsiveness is evaluated by patients on a categorical scale, their selfevaluation can be affected by the phenomenon of reporting heterogeneity (Rice et al. 2012). A few studies have investigated how standard socio-demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…This was the case of age, marital status, employment status, chronic illness, and experience. In line with the literature [33,34], our findings indicated that some individuals' socioeconomic characteristics were correlated with self-reported experience of the health service. For example, gender was statistically significant only for primary care.…”
Section: Resultssupporting
confidence: 90%
“…This was the case of age, marital status, employment status, chronic illness, and experience. In line with the literature [33,34], our findings indicated that some individuals' socioeconomic characteristics were correlated with self-reported experience of the health service. For example, gender was statistically significant only for primary care.…”
Section: Resultssupporting
confidence: 90%
“… 6 On the other hand, multiple influences (such as population’s sociodemographic characteristics of) were thought to play greater role in shaping people’s satisfaction, thus making it a less appropriate reflection of real service quality. 44 61 63 In other words, both responsiveness and satisfaction are shaped by characteristics of both people and systems and differences exist in degrees to which these characteristics affect self-assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Most of previous studies on health system responsiveness have focused on the demand‐side by investigating the association between sociodemographic characteristics of patients and their reported level of responsiveness. Some of these studies have adopted an international comparison perspective (e.g., Rice, Robone, & Smith, ; Sirven, Santos‐Eggimann, & Spagnoli, ; Valentine, Darby, & Bonsel, ), whereas others have adopted a national one (Adesanya et al, ; Ebrahimipour et al, ; Fiorentini, Ragazzi, & Robone, ; Luo, Wang, Lu, & Liu, ; Röttger, Blümel, Fuchs, & Busse, ). However, little is yet known about the influence of supply‐side factors on responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The use of data at disaggregated level has been shown of paramount importance to increase the reliability of analyses about hospital systems, because it allows, for example, to take into account differences in accounting principles and in the definitions in the outcomes of interest, which may exist across different observational units (e.g., health‐care providers) (Gravelle & Backhouse, ; Rice, Robone, & Smith, ). Earlier work has shown that hospital characteristics play an important role in explaining differences in patients' evaluation of healthcare (e.g., Fiorentini et al, ; Robone, Fiorentini, Nicoli, & Rodella, ; Sjetne, Veenstra, & Stavem, ; Young, Meterko, & Desai, ). However, differently from previous studies on responsiveness, which treated hospitals as “black‐boxes,” the present paper investigates which supply factors affect responsiveness not only across hospitals but also within hospitals.…”
Section: Introductionmentioning
confidence: 99%